2017
DOI: 10.1039/c7ra05738e
|View full text |Cite
|
Sign up to set email alerts
|

Progress in polydimethylsiloxane-modified waterborne polyurethanes

Abstract: Using polydimethylsiloxane (PDMS) to modify waterborne polyurethane (WPU) has proved to be an effective and feasible way to improve some key properties of WPU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 75 publications
(129 reference statements)
0
21
1
Order By: Relevance
“…Polydimethylsiloxane (PDMS) has many applications due to its unique properties, which mainly arise from its structure composed of organic grafted methyl group and inorganic SiO bond. These significant properties include great molecular flexibility, low surface energy, good hydrophobicity, flame retardancy, and so forth . PDMS had been widely added to PU to improve mechanical properties and surface and bulk properties .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polydimethylsiloxane (PDMS) has many applications due to its unique properties, which mainly arise from its structure composed of organic grafted methyl group and inorganic SiO bond. These significant properties include great molecular flexibility, low surface energy, good hydrophobicity, flame retardancy, and so forth . PDMS had been widely added to PU to improve mechanical properties and surface and bulk properties .…”
Section: Introductionmentioning
confidence: 99%
“…These significant properties include great molecular flexibility, low surface energy, good hydrophobicity, flame retardancy, and so forth . PDMS had been widely added to PU to improve mechanical properties and surface and bulk properties . In the study of the chemical modification of polyamide 12 (PA12) through the reaction with a hydride‐terminated PDMS, it was found that the mechanical properties and thermal stability of PA12 were enhanced .…”
Section: Introductionmentioning
confidence: 99%
“…Introducing organosilicon compounds into polymer melts and solutions is a rather common direction in modern polymer science and technology, as described in reviews (see, for example, [1]). As a rule, this approach is stipulated by wishing to combine, in one product, carbon chain polymers and silicate fragments that in some cases are important to reach the desired functional properties of the hybrid materials in practice [2].…”
Section: Introductionmentioning
confidence: 99%
“…Poly-dimethyl siloxane (PDMS or silicone) can bring profound property changes to these hybrids. 8 Hydroxyl-terminated poly-dimethyl siloxane (PDMS-OH) reacted with nucleophilic 3-glycidoxy propyl tri-methoxy silane (TMSepoxy) resin systems. However, the reaction is complicated by the inherent insolubility of silicone in organic resins.…”
Section: Introductionmentioning
confidence: 99%